2003
DOI: 10.1189/jlb.0803378
|View full text |Cite
|
Sign up to set email alerts
|

The significance of carbohydrates on G-CSF: differential sensitivity of G-CSFs to human neutrophil elastase degradation

Abstract: It has been reported recently that granulocyte-colony stimulating factor (G-CSF) is degraded upon exposure to human neutrophil elastase (HNE), and this has a negative effect on the ability of the cytokine to promote the in vitro proliferation and maturation of CD34+ cells. This has important implications on the possible in vivo role of elastase in providing negative feedback to granulopoiesis by the direct antagonism of G-CSF. The cytokine used in that study was expressed in Escherichia coli [and was nonglycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 43 publications
(37 reference statements)
1
25
1
2
Order By: Relevance
“…[27][28][29] Other studies have shown that G-CSF is degraded by serum enzymes, particularly elastases. Carter et al 30 showed that glycosylation reduces this elastase-dependent inactivation. It may thus prolong G-CSF's activity and make it more effective.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Other studies have shown that G-CSF is degraded by serum enzymes, particularly elastases. Carter et al 30 showed that glycosylation reduces this elastase-dependent inactivation. It may thus prolong G-CSF's activity and make it more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Digestion study of rhGCSF by hNE was performed according to Carter et al (2004a). Briefly 50 g ml −1 of purified rhGCSF protein preparations were incubated with 2 g ml −1 of hNE for 45 min at 37 • C with and without 2 mM PMSF, a known hNE inhibitor for comparison purposes.…”
Section: Degradation Of Rhgcsf By Human Neutrophil Elastase (Hne)mentioning
confidence: 99%
“…It is mainly produced by monocytes and macrophages (Bahrami et al, 2007) and stimulates proliferation, activation and differentiation of committed precursor cells of neutrophil lineage and mature neutrophils (Fallah et al, 2003). It is effectively used for the treatment of various forms of neutropenia, leukopenia, AIDS and bone marrow transplantation (Carter et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…95 Another possibility is that mislocalized NE retains some proteolytic activity and inappropriately attacks an opportunistic substrate it would not ordinarily encounter. Potential substrates, each capable of being proteolyzed by NE, located in the vicinity of the plasma membrane, and capable of regulating hematopoiesis, include G-CSF, [96][97][98] the G-CSF receptor, 97 the c-KIT receptor, 99 and Notch proteins. 95 Regardless of the precise molecular mechanism, mislocalized (or misfolded) NE must somehow drastically reduce the production of neutrophils from the progenitor cells in the bone marrow.…”
Section: A Model Of Neutropenia Based On Mispartitioning Between Granmentioning
confidence: 99%